Sustainable Aquaculture Techniques 2014
DOI: 10.5772/57196
|View full text |Cite
|
Sign up to set email alerts
|

Use of Yeasts as Probiotics in Fish Aquaculture

Abstract: Yeasts are unicellular eukaryotic microorganisms that are taxonomically placed within the phyla Ascomycota and Basidiomycota within the Kingdom Fungi [7]. Ascomycete yeasts comprise approximately 1,000 phylogenetically diverse species that have recently been assigned to 14 different lineages on the basis of multigene sequence analysis [8]. The other species of yeasts are classified as the basidiomycetes [9]. Some of the general characteristics and ecological properties of each phylum include the following: 1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
81
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 155 publications
(140 reference statements)
1
81
1
Order By: Relevance
“…However, it was unexpected to find low abundances of D. hansenii in the present study (0–33%; Fig. ), since it is the most frequently isolated yeast from fish (Navarrete and Tovar‐Ramírez ). In addition, it was unexpected that D. hansenii was not found in the gut mucosa, since this yeast has been shown to adhere to the gut mucus in rainbow trout (Vazquez‐warez et al .…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…However, it was unexpected to find low abundances of D. hansenii in the present study (0–33%; Fig. ), since it is the most frequently isolated yeast from fish (Navarrete and Tovar‐Ramírez ). In addition, it was unexpected that D. hansenii was not found in the gut mucosa, since this yeast has been shown to adhere to the gut mucus in rainbow trout (Vazquez‐warez et al .…”
Section: Discussioncontrasting
confidence: 49%
“…Studies have shown that feeding low inclusions rates (e.g. 10 g kg −1 ) of live yeast have a probiotic effect on gut microbiota that improves growth, feed efficiency, immune response of several fish species (Navarrete and Tovar‐Ramírez ; Hoseinifar et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the body weight increase in the other groups fed with high-cholesterol diet supplemented with cereal-based functional food could have been contributed by yeasts due to their growth promoting potentials. Yeasts are well-known for the secretion of polyamines, compounds that promote cell differentiation and maturation (Naverrete & Tovar-Ramirez, 2014). This make yeasts important feed supplements in animal husbandries to improve the growth and performance of animals (Li et al, 2006;Sharifuzzaman, Al-Harbi, & Austin, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, probiotics or beneficial bacteria are known to control pathogens through a variety of mechanisms and affect intestinal microbial communities (Kesarcodi‐Watson et al . ; Navarrete & Tovar‐Ramírez ; Newaj‐Fyzul et al . ).…”
Section: Introductionmentioning
confidence: 99%